Ten simple rules to facilitate evidence implementation in the environmental sciences - Christopher J. Lortie; Malory Owen (Canadian Science Publishing, 2020)
There is a gap between fundamental science and managers. There are many general solutions including the need to better leverage the primary scientific literature for decision-making. Herein, we provide a list of 10 simple rules to support environmental management through better scientific writing and suggest practices for more transparent publications. These rules can also be used as a checklist for reusing the primary literature when searching for relevant evidence in the environmental sciences. We need to better structure knowledge in papers for connections within sustainable societies.